Kombinasi Pakan Limbah Kulit Pisang dan Kulit Ari Kedelai terhadap Bobot Larva Hermetia illucens (BSF) dan Indeks Pengurangan Sampah - rida nur afifah; Dyah Rini Indriyanti; Priyantini Widiyaningrum; Ning Setiati (Life Science, 2023)
Hermetia illucens, often called BSF larvae, is an insect that has a high enough protein content so that it becomes an alternative animal feed that fulfills a high and quality protein source for animal feed. Bioconversion that utilizes organic materials by involving living organisms. Utilization of waste materials from banana peels and soybean husks as feed media for BSF larvae. This study aims to analyze the results of feeding a combination of banana peels and soybean epidermis on weight, waste reduction index and protein and fat content in BSF larvae. This study used an experimental method with the RAL technique (completely randomized design) with five treatments and four repetitions A : 100% banana peel waste, B : 75% banana peel + 25% soybean husk, C : 50% epidermis + 50% peel banana, D : 25% banana peel + 25% soybean epidermis, E : 100% soybean epidermis using 2kg of feed medium for each treatment. The results showed that the heaviest final weight was in treatment D (25% banana peel and 75% soybean epidermis) with an average final larval weight of 0.15 grams, the waste reduction index was 3.78%/day. The highest protein content in this study was in treatment A (100% banana peel) namely 48.97% and the highest fat content was in treatment D (25% banana peel and 75% soybean husk) namely 32.69%.